Jūratė Baranova and the Way of Philosophy to the Lithuanian School - Duoblienė, Lilija (Problemos, 2022)
The article analyses the contribution of Professor Jūratė Baranova to the introduction of philosophy teaching into the Lithuanian general school. There is a discussion about the need of philosophy teaching, the initiatives of Baranova and her colleagues’ mutual activities preparing textbooks and other teaching tools. The courses initiated, the philosophy education programmes for teachers and teacher re-skilling programmes, as well as students’ Philosophy Olympiads are presented.  The educational projects of Baranova and her co-authors are reviewed, focusing on teaching cultural literacy at school whilst using dialogue, argumentation and multimodality. The author concludes that Baranova was one of the key contributors amongst Lithuanian professors and teachers, who made an input to the introduction and development of philosophy education at schools.
Keywords: philosophy; teachers; textbooks; Olympiad; Jūratė Baranova